The central Onodi cell: A previously unreported anatomic variation - Cherla, Deepa V. (OceanSide Publications, Inc., 2013)
Preoperative recognition of the Onodi cell is necessary to avoid injury to closely associated structures, including the internal carotid artery and the optic nerve. This article describes the central Onodi cell, a variation in which a posterior ethmoid cell lies superior to the sphenoid sinus in a midline position with at least one optic canal bulge. To our knowledge, this anatomic variation has not been previously reported in the literature. Radiographic and endoscopic imaging of this unique variation is provided.